Implementation Of “3 In A Row” For Business Excellence In Industries - Zia, Tauseef Siddiqui; Khan, Anna (Universiti Sains Malaysia, 2016)
Three in a row which brings at least 3 levels of people in the organization together as a team to continually improve their areas performance in Sustainability, Quality, Environment and Operation management. The team which meet at prefixed regular interval decides what checks are to be made that will contribute in improving the company‘s declared policy of sustainability, quality, environmental and health and safety management thus strongly supports directly or indirectly in the sustainable development. The team is normally led by the senior most persons depending on the level of employees present who acts as a leader and a coach for the team to guide, educate and motivate the team. Various check lists are made based on the Company‘s best practices, procedures and regulatory requirements on Sustainability, Quality Environmental and Safety Management. The area is also inspected by the team and any nonconformance and deviation from the best practices are observed it is noted and highlighted.